The influence of store environment on brand attitude, brand experience and purchase intention - Marike Venter de Villiers; Richard Chinomona; Tinashe Chuchu (South African Journal of Business Management, 2018)
Background: Consumer decision-making is shifting from the rational to the emotional, and as a result, retailers are investing in unique store atmospheric cues to capture the attention of consumers. Although not a completely new phenomenon, a lack of studies on this topic remains in Africa, an emerging economy that is rapidly becoming part of the global economy. This is especially evident in the fashion industry where global fashion chain stores are rapidly infiltrating the local market. Objectives: This article aims to investigate the influence of store environment on purchase intention of fashion products with brand attitude and brand experience as the mediators. Method: By means of a quantitative study, 501 online self-administered surveys were distributed among black middle-class women residing in Johannesburg. Results: The results support four of the five hypotheses. It is therefore evident that store environment positively influences consumer's brand attitudes, purchase intention and brand experience in the fashion retail industry. Conclusion: This article contributes to existing literature on fashion retail, experiential marketing and branding. It further provides retailers with adequate insight into experiential retail strategies that can yield profitable returns and increase their customer loyalty base.
Keywords: 650